2012
DOI: 10.1002/adfm.201201265
|View full text |Cite
|
Sign up to set email alerts
|

Fouling Characteristics and Electrochemical Recovery of Carbon Nanotube Membranes

Abstract: The fouling behavior of carbon nanotube (CNT) membranes is investigated for large protein biomolecules and a wide variety of small molecules. The CNT membranes are largely fouling resistant, even to untreated river water, due to size exclusion and an inert graphitic core that supports fast fluid flow. However, it is found that bovine serum albumin (BSA) and naphthalene significantly foul membranes due to solution coagulation and π–π stacking, respectively. Small single‐walled (SW) CNTs (<1.5 nm i.d.) are di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 39 publications
1
45
0
Order By: Relevance
“…A few previous reports investigated fouling behavior and biomolecule rejection by vertically aligned CNT pores for application in water purification. Consistently with our results for viral filtration by 3.3 nm SWNTs, these studies demonstrated complete size‐exclusion of micron‐sized bacteria and partial or complete rejection of bovine serum albumin (≈7 nm diameter) by multi‐ (MW) and SW‐ or double‐walled nanotubes, respectively. Buckypaper membranes were also reported to efficiently remove viruses and bacteria from aqueous solutions .…”
supporting
confidence: 90%
“…A few previous reports investigated fouling behavior and biomolecule rejection by vertically aligned CNT pores for application in water purification. Consistently with our results for viral filtration by 3.3 nm SWNTs, these studies demonstrated complete size‐exclusion of micron‐sized bacteria and partial or complete rejection of bovine serum albumin (≈7 nm diameter) by multi‐ (MW) and SW‐ or double‐walled nanotubes, respectively. Buckypaper membranes were also reported to efficiently remove viruses and bacteria from aqueous solutions .…”
supporting
confidence: 90%
“…Antifouling properties of the membranes were also evaluated using bovine serum albumin (BSA) as a model foulant, which is the most commonly used protein foulant for the antifouling tests5657585960616263. Figure 3c presents the time-dependent normalized water flux variations of the NF2A, C-PIM-1, and PC-PIM-1 membranes during the filtration of a BSA solution.…”
Section: Resultsmentioning
confidence: 99%
“…2 Among all the membrane materials, carbon nanotubes (CNTs) have been considered as a good option due to their mechanical stability, flexibility, and chemical resistivity. Previous results have demonstrated that CNT-based electrochemical filters were effective in removing aqueous organic pollutants, such as salts, 6,7 proteins, 8 viruses, 9 azo dyes, 10 pharmaceuticals, 11,12 perfluorinated chemicals, 13 and phenol. 5 An electrochemical CNT filter brings this concept one step further by not only adsorptively trapping, but also electrochemically oxidizing the target compounds.…”
Section: Introductionmentioning
confidence: 99%